Psychological Dynamics of Forming Cognitive Map Arabic Translation in Student - Mahsus, Muhammad; Kusumaputri, Erika Setyanti (International Journal of Islamic Educational Psychology, 2022)
A translation is a cognitive activity, while humans, as cognitive subjects, have different ways of thinking. This condition has implications for the difference in translation results; infrequently, the translation results need to be clarified for the reader. Therefore, investigating the problems of learning Arabic must be done to minimize a generation of incompetent Arabic translators. This study aims to investigate the psychological dynamics in a person that cause differences in the way of thinking in Arabic translation. This research is qualitative research using a multi-case approach. The research subjects comprised 10 Nurul Ummah students as a single-case analysis and 4 LSQ Ar-Rohmah students as a cross-case analysis. The data collection technique used interviews and documentation to assess translated results by expert Arab-Indo translators. Data processing to data visualization implemented NVivo 12 Plus analyzing the suitability of patterns between single and cross-case cases by synchronizing interview transcription results and translated values. Data analysis found several problems that caused differences in participants’ thinking in Arabic translation: First, the difference in the weak structural representation of nahwu-shorof due to the difference in the age of knowledge acquisition, the number of activities participated in by participants, and the selection of the priority scale of selected activities; second, differences in inferential planning accuracy due to differences in participant habituation in Arabic translation.